Kemampuan Berpikir Kreatif Matematika Siswa Ditinjau dari Aspek Kefasihan, Fleksibilitas, dan Kebaruan - Marhayati, Marhayati (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The purpose of this study was to assess the ability mathematics creative thinking terms of aspects of fluency, flexibility, and novelty for fifth grade students at elementary school. Applied learning in this study through learning mathematics problems posing. Students are said to be creative in mathematics problem posing if the students meet the problems posed aspects of fluency, flexibility, and novelty. Based on the analysis of mathematics problem posing task, especially for questions that can be solved math students, can be grouped into four categories: the question does not contain any new information, it does not contain new information and simplify the mathematical complexity, contain new information, as well as containing new information and develop a form of inquiry. The analysis showed that most students tend to only meet the fluency component only and some also cater fluency component. The conclusion of this study is that the fifth grade students have the ability mathematics creative thinking enough.